2022
DOI: 10.3389/fmolb.2022.968248
|View full text |Cite
|
Sign up to set email alerts
|

HSP70 and their co-chaperones in the human malaria parasite P. falciparum and their potential as drug targets

Abstract: As part of their life-cycle, malaria parasites undergo rapid cell multiplication and division, with one parasite giving rise to over 20 new parasites within the course of 48 h. To support this, the parasite has an extremely high metabolic rate and level of protein biosynthesis. Underpinning these activities, the parasite encodes a number of chaperone/heat shock proteins, belonging to various families. Research over the past decade has revealed that these proteins are involved in a number of essential processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Among the 29 quantified parasitic proteins, we identified HSP70 ( PF3D7_0917900 ), involved in protein refolding and the glycolysis protein enolase ( PF3D7_1015900 ). Parasitic chaperone proteins like HSP70 are parasite survival factors, counteracting several biological host reactions including fever, degradation or immune system response (Barth et al, 2022 ), and contribute to P. falciparum virulence (Shonhai and Blatch, 2021 ). The glyceraldehyde-3-phosphate dehydrogenase ( GAPDH ; PF3D7_1462800 ) was quantified only in the SM groups (Dataset EV9 ), representing an indirect reflection of increased protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 29 quantified parasitic proteins, we identified HSP70 ( PF3D7_0917900 ), involved in protein refolding and the glycolysis protein enolase ( PF3D7_1015900 ). Parasitic chaperone proteins like HSP70 are parasite survival factors, counteracting several biological host reactions including fever, degradation or immune system response (Barth et al, 2022 ), and contribute to P. falciparum virulence (Shonhai and Blatch, 2021 ). The glyceraldehyde-3-phosphate dehydrogenase ( GAPDH ; PF3D7_1462800 ) was quantified only in the SM groups (Dataset EV9 ), representing an indirect reflection of increased protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…There is substantial evidence that PfHSPs are not only genuine drug targets but that they also carry highly druggable structural features for antimalarial drug discovery. 9 , 10 , 11 HSPs were discovered on the basis that their expression was significantly upregulated in response to physical, chemical, or physiological stress factors, and they were named according to their apparent molecular weight; for example, HSP70 (HSP70) is a 70 kDa protein. The major families of HSPs (HSP10, HSP40, HSP60, HSP70, HSP90, and HSP100) have now been shown to play essential roles in cell survival not only under stressful conditions but also under normal physiology, with many of them demonstrated to be molecular chaperones with both inducible and constitutive isoforms.…”
Section: Malarial Hsps and Their Complexes As Drug Targetsmentioning
confidence: 99%
“… 44 PfHSP70-1 is an abundant chaperone of the parasite cytosol that is required for survival. 10 Known inhibitors of PfHSP70-1 include polymyxin B and (−)-epigallocatechin-3-gallate, both of which bind with high affinity (submicromolar) to the full-length protein and a nucleotide-binding domain (NBD) construct, suggesting that the primary bind site is the N-terminal ATPase domain ( Table 1 ). 28 , 29 Similarly, the phytocompound iso-mukaadial acetate inhibits the basal ATPase activity of PfHSP70-1, 30 while malonganenones, including malonganenone A, B, and C, and 1,4 naphthoquinones, particularly lapachol and its derivatives, have been reported to inhibit the protein aggregation suppression activity of PfHSP70-1 ( Table 1 ).…”
Section: Malarial Hsps and Their Complexes As Drug Targetsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been relatively few small molecule inhibitor studies on PfJDP-PfHsp70 interactions in general ( Daniyan and Blatch, 2017 ; Barth et al, 2022 ), and even fewer studies that have identified specific small molecule inhibitors of the PfJDP-stimulated PfHsp70 ATPase activity or PfJDP-stimulated chaperone activity of PfHsp70s ( Dutta et al, 2021b ; Almaazmi et al, 2022 ). Small molecule compounds have been identified that inhibit the PfJDP-stimulated ATPase activity and not the basal ATPase activity of parasite-resident PfHsp70-1 (pyrimidinone DMT2264; Botha et al, 2011 ) and exported PfHsp70-x (malonganenone A; Cockburn et al, 2014 ).…”
Section: The Exported Pfjdp-pfhsp70 Complex Is a Potential Drug Targetmentioning
confidence: 99%